The P16 rootstock inhibits the growth but enhances the fruit quality of "Jonagored" apples when grown under warm summer conditions - Blanco, A.=700 1 Mata, A.P.; Lasaosa, A.; Val, J.
(Es, En)
Ilus., 19 ref.
Keywords: MALUS PUMILA; PORTAINJERTOS; COLOR; FRUTO; PIGMENTOS; INHIBIDORES DEL CRECIMIENTO; ESPAÑA; PATRONES ENANIZANTES P16; SPANISH JOURNAL OF AGRICULTURAL RESEARCH